Fixed point theorem for generic 2-generalized hybrid mappings in Hilbert spaces - Kondo, Atsumasa (Topological Methods in Nonlinear Analysis, 2022)
We establish a fixed point theorem for a class of mappings called generic2-generalized hybrid mappings in the setting of a real Hilbert space. Twoexamples of that class of mappings are presented herein. The mappings arenot quasi-nonexpansive even though they have fixed points. One of thesemaps is even not continuous. The fixed point theorem proved in this articleimproves many previous works in the literature.